Regulation of Apetala2/Ethylene Response Factors in Plants - Phukan, Ujjal J.; Jeena, Gajendra S.; Tripathi, Vineeta; Shukla, Rakesh K. (Frontiers in Plant Science, 2017)
Multiple environmental stresses affect growth and development of plants. Plants try to adapt under these unfavorable condition through various evolutionary mechanisms like physiological and biochemical alterations connecting various network of regulatory processes. Transcription factors (TFs) like APETALA2/ETHYLENE RESPONSE FACTORS (AP2/ERFs) are an integral component of these signaling cascades because they regulate expression of a wide variety of down stream target genes related to stress response and development through different mechanism. This downstream regulation of transcript does not always positively or beneficially affect the plant but also they display some developmental defects like senescence and reduced growth under normal condition or sensitivity to stress condition. Therefore, tight auto/cross regulation of these TFs at transcriptional, translational and domain level is crucial to understand. The present manuscript discuss the multiple regulation and advantage of plasticity and specificity of these family of TFs to a wide or single downstream target(s) respectively. We have also discussed the concern which comes with the unwanted associated traits, which could only be averted by further study and exploration of these AP2/ERFs.